HIGH-TEMPERATURE OXIDATION BEHAVIOUR OF Fe11Al BASED ALLOYS - Syahril Syahril; Wagiyo H; Bambang Sugeng; Ari Handayani (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2003)
HIGH-TEMPERATURE OXIDATION BEHAVIOUR OF Fe11Al BASED ALLOYS. Thermomechanically treated Fe11Al based alloys were isothermally oxidised in air at 900, 1000 and 1100 °C respectively. Their oxidation behaviour was studied using thermogravimetric analyser (TGA), X-ray diffractometer (XRD), and scanning electron microscope (SEM). It was found that the oxide scales formed on alloys studied consisted mainly of α- and θ-Al2O3. Additions of 0.5 wt. % Nb and Mo significantly improved the oxidation resistance of the alloys.